Measurement of the normalized Z/gamma* -> mu(+)mu(-) transverse momentum distribution in p(p)over-bar collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aleexev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Ancu, L. S.; et al. (Elsevier B.V., 2010)
We present a new measurement of the Z/gamma* transverse momentum distribution in the range 0-330 GeV, in proton-antiproton collisions at root s = 1.96 TeV. The measurement uses 0.97 fb(-1) of integrated luminosity recorded by the D0 experiment and is the first using the Z/gamma* -> mu(+)mu(-) + X channel at this center-of-mass energy. This is also the first measurement of the Z/gamma* transverse momentum distribution that presents the result at the level of particles entering the detector, minimizing dependence on theoretical models. As any momentum of the Z/gamma* in the plane transverse to the incoming beams must be balanced by some recoiling system, primarily the result of QCD radiation in the initial state, this variable is an excellent probe of the underlying process. Tests of the predictions of QCD calculations and current event generators show they have varied success in describing the data. Using this measurement as an input to theoretical predictions will allow for a better description of hadron collider data and hence it will increase experimental sensitivity to rare signals. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Z bosons; Differential cross section; Perturbative QCD; Event generators; Monte Carlo models